Light-absorbing composition and optical filter

JP7644185B2Active Publication Date: 2025-03-11NIPPON SHEET GLASS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023142225
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-11
Estimated Expiration
2039-11-06

AI Technical Summary

Benefits of technology

【0012】 上記の光吸収性組成物は、短波長領域の吸収特性の観点から有利である。加えて、上記の光吸収膜及び上記の光学フィルタは、短波長領域の吸収特性の観点から有利である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644185000009
    Figure 0007644185000009
  • Figure 0007644185000010
    Figure 0007644185000010
  • Figure 0007644185000011
    Figure 0007644185000011
Patent Text Reader

Abstract

To provide a light absorbing composition which is advantageous in terms of absorption properties in a short-wavelength region.SOLUTION: A light absorbing composition of the present invention contains a phosphonic acid, an ultraviolet absorbing agent having a hydroxyl group and carbonyl group within a molecule thereof, and a metal component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a light-absorbing composition, a light-absorbing film, and an optical filter. [Background technology]

[0002] CCD (Charge Coupled Device) or CMOS (Complementary Metal Oxide Semiconductor) In imaging devices using solid-state imaging elements such as the IR-1000 and IR-10000 series, various optical filters are arranged in front of the solid-state imaging element in order to obtain images with good color reproducibility. In general, solid-state imaging elements have spectral sensitivity in a wide wavelength range from the ultraviolet region to the infrared region. Meanwhile, human visual sensitivity exists only in the visible light region. For this reason, a technique is known in which an optical filter that blocks part of infrared or ultraviolet light is arranged in front of the solid-state imaging element in order to bring the spectral sensitivity of the solid-state imaging element in the imaging device closer to the human visual sensitivity.

[0003] Conventionally, such optical filters generally use light reflection by a dielectric multilayer film to block infrared or ultraviolet rays. Meanwhile, in recent years, optical filters with a film containing a light absorbent have been attracting attention. The transmittance characteristics of an optical filter with a film containing a light absorbent are not easily affected by the angle of incidence, so that even if light is obliquely incident on the optical filter in an imaging device, a good image with little change in color can be obtained. In addition, a light-absorbing optical filter that does not use a light-reflecting film can suppress the occurrence of ghosts and flares caused by multiple reflections by the light-reflecting film, so that good images can be easily obtained in backlit conditions or when photographing night scenes. In addition, an optical filter with a film containing a light absorbent is also advantageous in terms of miniaturizing and thinning an imaging device.

[0004] As such a light absorbing agent, a light absorbing agent formed by phosphonic acid and copper ions is known. For example, Patent Document 1 describes an optical filter having a light absorbing layer containing a light absorbing agent formed by phosphonic acid having a phenyl group or a halogenated phenyl group (phenyl-based phosphonic acid) and copper ions.

[0005] Patent Document 2 also describes an optical filter having a UV-IR absorbing layer capable of absorbing infrared and ultraviolet rays. The UV-IR absorbing layer contains a UV-IR absorbent formed of phosphonic acid and copper ions. In order for the optical filter to meet certain optical properties, the UV-IR absorbing composition contains, for example, a phenyl-based phosphonic acid and a phosphonic acid having an alkyl group or a halogenated alkyl group (alkyl-based phosphonic acid).

[0006] Furthermore, Patent Document 3 describes an infrared cut filter including an organic dye-containing layer that contains a specific organic dye, and a copper phosphonate-containing layer. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2018 / 088561 [Patent Document 2] Patent No. 6232161 [Patent Document 3] International Publication No. 2017 / 006571 Summary of the Invention [Problem to be solved by the invention]

[0008] The techniques described in Patent Documents 1 to 3 need to be reconsidered from the viewpoint of absorption characteristics in the short wavelength region around 400 nm. Therefore, the present invention provides a light-absorbing composition, a light-absorbing film, and an optical filter that are advantageous from the viewpoint of absorption characteristics in the short wavelength region. [Means for solving the problem]

[0009] The present invention relates to 1. A light absorbing composition comprising a resin and a light absorbing compound dispersed in the resin, In the transmission spectrum of the light-absorbing film formed by the light-absorbing composition at an incident angle of 0 degrees, the transmittance at a wavelength of 400 nm is defined as T 400 The transmittance at a wavelength of 550 nm is T 550 The transmittance at a wavelength of 800 nm is T 800 Then, 8≦T 550 / T 400 and 8≦T 550 / T 800 Fulfilling A light absorbing composition is provided.

[0011] The present invention also provides a method for producing a semiconductor device comprising the steps of: An optical filter including a light absorbing film including a resin and a light absorbing compound, In the transmission spectrum of the optical filter at an incident angle of 0 degrees, the transmittance at a wavelength of 400 nm is defined as T 400 The transmittance at a wavelength of 550 nm is T 550 The transmittance at a wavelength of 800 nm is T 800 Then, 8≦T 550 / T 400 and 8≦T 550 / T 800 Fulfilling An optical filter is provided. Effect of the Invention

[0012] The light-absorbing composition is advantageous in terms of absorption characteristics in the short wavelength region. In addition, the light-absorbing film and the optical filter are advantageous in terms of absorption characteristics in the short wavelength region. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a light absorbing film according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of an optical filter according to the present invention. [Diagram 3] FIG. 3 shows the transmission spectrum of the optical filter according to the first embodiment. [Figure 4]FIG. 4 shows the transmission spectrum of the optical filter according to the second embodiment. [Diagram 5] FIG. 5 shows the transmission spectrum of the optical filter according to the third embodiment. [Figure 6] FIG. 6 shows the transmission spectrum of the optical filter according to the fourth embodiment. [Figure 7] FIG. 7 shows the transmission spectrum of the optical filter according to Comparative Example 1. As shown in FIG. [Figure 8] FIG. 8 shows the transmission spectrum of the optical filter according to Comparative Example 2. As shown in FIG. [Figure 9] FIG. 9 shows the transmission spectrum of the optical filter according to Comparative Example 3. As shown in FIG. [Figure 10] FIG. 10 shows the transmission spectrum of the optical filter according to Comparative Example 4. As shown in FIG. [Figure 11] FIG. 11 shows the transmission spectrum of a transparent glass substrate. [Figure 12] FIG. 12 is an LC-UV chromatograph of ethanol containing a fragment of the light-absorbing film according to Example 5. [Figure 13] FIG. 13 is an absorption spectrum of the characteristic peaks in the LC-UV chromatograph shown in FIG. [Figure 14] FIG. 14 shows a transmission spectrum of an ethanol solution in which the ultraviolet absorbing agent is dissolved from a fragment of the light absorbing film according to Example 5. [Figure 15] FIG. 15 shows the transmission spectra of five types of ethanol solutions in which ultraviolet absorbents are dissolved at specified concentrations. [Figure 16] FIG. 16 is a graph showing the relationship between the value tr obtained by dividing the minimum transmittance by the maximum transmittance, based on the transmission spectrum shown in FIG. 15, and the concentration η [%] of the ultraviolet absorbing agent. [Figure 17] FIG. 17 shows a transmission spectrum of an ethanol solution in which the ultraviolet absorbing agent is dissolved from a fragment of the light absorbing film according to Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In an optical filter for an imaging device using a solid-state imaging element, if it can effectively absorb light in the short wavelength region around a wavelength of 400 nm in addition to absorbing light in the long wavelength region such as infrared rays, the value of the optical filter will be increased. According to the optical filter described in Patent Document 1, the wavelength at which the spectral transmittance is 50% in the wavelength range of 350 nm to 450 nm is 400 nm. nm. In addition, according to the optical filter described in Patent Document 2, the wavelength at which the spectral transmittance is 50% in the wavelength range of 350 nm to 450 nm is in the range of about 390 nm to 415 nm. Based on these facts, it is difficult to say that the optical filters described in Patent Documents 1 and 2 are advantageous in terms of effectively absorbing light in the short wavelength region around 400 nm. The infrared cut filter described in Patent Document 3 requires multiple light absorbing layers, namely an organic dye-containing layer and a copper phosphonate-containing layer. For this reason, it is difficult to say that the technology described in Patent Document 3 is advantageous in terms of simplifying the optical filter.

[0015] Therefore, the present inventors have conducted extensive research to develop a light-absorbing composition that contains phosphonic acid and a metal component and is advantageous in terms of effectively absorbing light in the short wavelength region around 400 nm. As a result of extensive trial and error, the present inventors have newly discovered that a light-absorbing composition that contains a specific ultraviolet absorber together with phosphonic acid and a metal component is advantageous in terms of effectively absorbing light in the short wavelength region, and have completed the present invention.

[0016] Hereinafter, an embodiment of the present invention will be described. Note that the following description is merely an example of the present invention, and the present invention is not limited to the following embodiment.

[0017] The light-absorbing composition according to the present invention contains a phosphonic acid, an ultraviolet absorber having a hydroxyl group and a carbonyl group in the molecule, and a metal component. Since the light-absorbing composition contains the ultraviolet absorber having a hydroxyl group and a carbonyl group in the molecule together with the phosphonic acid and the metal component, the light-absorbing film or optical filter produced using the light-absorbing composition tends to effectively absorb light in the wavelength region around 400 nm.

[0018] Advantageous conditions for an ultraviolet absorber include appropriate light absorption range and transmission range, photochemical stability, low photosensitizing effect within the range of use without any effect, and thermochemical stability. From this perspective, it is considered that the mechanism of light absorption of ultraviolet absorbers utilizes a hydrogen transfer reaction of a hydroxyl group in a molecule due to photoexcitation (intramolecular hydrogen abstraction reaction). Examples of ultraviolet absorbers that exhibit such a mechanism include compounds such as hydroxybenzophenone, salicylic acid, hydroxyphenylbenzotriazole, hydroxyphenyltriazine, and substituted acrylonitrile. In hydroxybenzophenone and salicylic acid, a reaction involving the transfer of hydrogen between a hydroxyl group and a carbonyl group contained in the molecule is involved in the light absorption of ultraviolet rays, etc. On the other hand, in hydroxyphenylbenzotriazole, hydroxyphenyltriazine, and substituted acrylonitrile, a reaction involving the transfer of hydrogen between a hydroxyl group and a nitrogen atom contained in the molecule is involved in the light absorption of ultraviolet rays, etc. These ultraviolet absorbers have a hydroxyl group in their molecules, so it is presumed that they will cause interactions such as partial complexation with a coexisting metal component or hydrogen donor. In a system such as a light-absorbing composition containing an ultraviolet absorber and its cured product, a case where an ultraviolet absorber having a hydroxyl group exists alone is compared with a case where a metal component or a hydrogen donor and an ultraviolet absorber having a hydroxyl group coexist. According to this comparison, differences arise in optical properties such as their light absorption spectrum and their light transmission spectrum, supporting the above speculation. In particular, it was found that in a light-absorbing film obtained by curing a light-absorbing composition containing phosphonic acid, an ultraviolet absorber having a hydroxyl group and a carbonyl group in the molecule, and a metal component, a phenomenon occurs in which the light absorption band at a wavelength of 300 to 500 nm shifts to the long wavelength side. For this reason, such a light-absorbing film is advantageous for effectively and appropriately absorbing light at a wavelength of around 400 nm. In addition, if the light absorption band shifts to the long wavelength side or expands to the long wavelength side, for example, a phenomenon in which the absorption maximum wavelength shifts to the long wavelength side within the wavelength range of 300 nm to 500 nm of the transmission spectrum, or a phenomenon in which the wavelength at which the transmittance is 50% (UV cutoff wavelength) shifts to the long wavelength side may become apparent.Thus, according to the light-absorbing composition of the present invention, the light-absorbing film which is the cured product thereof, and the optical filter including the light-absorbing film, the absorption characteristics inherent to the ultraviolet absorbent are short wave. As a result, the spectral transmittance of such a light absorbing film or optical filter tends to be more appropriate when used together with a solid-state image sensor or the like.

[0019] The arrangement of the hydroxyl group and the carbonyl group in the ultraviolet absorber is not limited to a specific arrangement. In the ultraviolet absorber, the hydroxyl group and the carbonyl group are preferably arranged with 1 to 6 atoms between them. This is thought to facilitate hydrogen transfer between the hydroxyl group and the carbonyl group in the ultraviolet absorber. Therefore, the phenomenon in which the light absorption band at wavelengths of 300 to 500 nm shifts to the long wavelength side is easily caused. As a result, the light absorbing film obtained by curing the light absorbing composition is more likely to effectively and appropriately absorb light at a wavelength of around 400 nm.

[0020] The light-absorbing film obtained by curing the light-absorbing composition according to the present invention has a transmission spectrum at an incident angle of 0 degrees, and a transmittance T 400 , at a wavelength of 550 nm Transmittance T 550 , and transmittance T at a wavelength of 800 nm 800 For example, 8≦T 550 / T 400 and 8≦T 550 / T 800 As a result, a light-absorbing film or optical filter produced using the light-absorbing composition is likely to exhibit high transmittance for visible light while appropriately absorbing ultraviolet and infrared rays in the wavelength region around the visible range.

[0021] Transmittance T 400 , transmittance T 550 , and transmittance T 800 Preferably, 12≦T 550 / T 400 and 28≦T 550 / T800 and more preferably 16≦T 550 / T 400 and 60≦T 550 / T 800 Meet the conditions.

[0022] The ultraviolet absorber is not limited to a specific ultraviolet absorber as long as it has a hydroxyl group and a carbonyl group in its molecule. The ultraviolet absorber is preferably a compound that is not likely to aggregate even when mixed with phosphonic acid and a metal component. Such an ultraviolet absorber includes, for example, at least hydroxybenzophenone.

[0023] The ultraviolet absorber preferably contains a benzophenone-based compound represented by the following formula (A1): In this case, a light-absorbing film or optical filter produced using the light-absorbing composition is more likely to effectively absorb light in the short wavelength region around 400 nm.

[0024] [ka]

[0025] In formula (A1), R 11 , R 12 , R 21 , and R 22 At least one of R is a hydroxy group. 11 , R 12 , R 21 , or R 22 When R is a functional group other than a hydroxy group, multiple R 11 , multiple R 12 , multiple R 21 , or multiple R 22 may be present, R 11 , R 12 , R 21 , and R 22 At least one of may not be present.

[0026] R 11 , R 12 , R 21 , or R 22is a functional group other than a hydroxy group, the functional group may be, for example, a carboxyl group, an aldehyde group, a halogen, an alkyl group having 1 to 12 carbon atoms, an alkyl group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms.

[0027] The ultraviolet absorber preferably contains a benzophenone-based compound represented by the following formula (A2): In this case, the light-absorbing film or optical filter produced using the light-absorbing composition is more likely to effectively absorb light in the short wavelength region around 400 nm.

[0028] [ka]

[0029] In formula (A2), R 31 may be a hydroxy group, a carboxyl group, an aldehyde group, a halogen, an alkyl group having 1 to 12 carbon atoms, an alkyl group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms. 31 In formula (A2), R 41 and R 42 may be a hydroxy group, a carboxyl group, an aldehyde group, a halogen, an alkyl group having 1 to 12 carbon atoms, an alkyl group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms in which one or more hydrogen atoms are substituted with halogen atoms. 41 and R 42 In formula (A2), a plurality of R 41 may be present, and multiple R42 may also be present.

[0030] The benzophenone compound represented by formula (A1) or formula (A2) is not limited to a specific compound. The benzophenone compound is, for example, at least one selected from the group consisting of 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-4'-chlorobenzophenone, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-n-octoxybenzophenone, 2-hydroxy-5-chlorobenzophenone, and 2,4-dibenzoylresorcin.

[0031] The phosphonic acid is not limited to a specific phosphonic acid. The light-absorbing composition may contain a single type of phosphonic acid or may contain multiple types of phosphonic acid. The phosphonic acid is represented by, for example, the following formula (B). In this case, the light-absorbing film or optical filter produced using the light-absorbing composition effectively absorbs light in a wavelength range longer than 750 nm, and more reliably absorbs light in a short wavelength range around 400 nm.

[0032] [ka]

[0033] In formula (B), R3 is an alkyl group, at least one hydrogen atom in the alkyl group. The halogen atom is a halogenated alkyl group in which at least one hydrogen atom is substituted with a halogen atom, an aryl group, or a halogenated aryl group in which at least one hydrogen atom in an aryl group is substituted with a halogen atom.

[0034] The phosphonic acid represented by formula (B) is not limited to a specific phosphonic acid. The phosphonic acid represented by formula (B) may be methylphosphonic acid, ethylphosphonic acid, normal (n-) propylphosphonic acid, isopropylphosphonic acid, normal (n-) butylphosphonic acid, isobutylphosphonic acid, secbutylphosphonic acid, tertbutylphosphonic acid, phenylphosphonic acid, or the like phosphonic acid, or may be the above phosphonic acid in which at least one hydrogen atom is replaced with a halogen atom, such as bromomethylphosphonic acid, fluoroethylphosphonic acid, bromophenylphosphonic acid, and iodophenylphosphonic acid.

[0035] The metal component is not limited to a specific metal component. The metal component is, for example, a copper component. In this case, the light-absorbing film or optical filter produced using the light-absorbing composition is more likely to effectively absorb light in the short wavelength region around 400 nm. In the light-absorbing composition, the metal component may be present as a metal ion, or may be present in a state of forming a complex with a specific compound. The source of the metal component is not limited to a specific compound. The source of the metal component is, for example, acetate, benzoate, formate, stearate, pyrophosphate, oxide, chloride, hydroxide, or a hydrated salt thereof.

[0036] In the light-absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the metal component is not limited to a specific value. The ratio is, for example, 0.001 to 0.100, preferably 0.001 to 0.030, based on the amount of substance. This makes it easier for the light-absorbing film or optical filter produced using the light-absorbing composition to more reliably and effectively absorb light in the short wavelength region around 400 nm.

[0037] In the light-absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the phosphonic acid is not limited to a specific value. The ratio is, for example, 0.1% to 5%, preferably 0.1% to 3%, and more preferably 0.1% to 1% by mass. This makes it easier for the light-absorbing film or optical filter produced using the light-absorbing composition to more reliably and effectively absorb light in the short wavelength region around 400 nm.

[0038] In the light absorbing composition, a particulate light absorber may be formed by the reaction of phosphonic acid with a metal component, or by the reaction of any one of phosphonic acid, a metal component, and an ultraviolet absorber. For example, a phosphonic acid-copper compound formed by the reaction of phosphonic acid with a copper component is an infrared absorber. The average particle diameter of the particulate light absorber is, for example, 5 nm to 200 nm. If the average particle diameter of the particulates is 5 nm or more, no special process is required for the fineness of the particulates, and the structure of the particulates containing at least the light absorbent is less likely to be broken. In addition, the particulates are well dispersed in the light absorbing composition. In addition, if the average particle diameter of the particulates is 200 nm or less, the effect of Mie scattering can be reduced, the transmittance of visible light can be improved in the light absorbing film, and the deterioration of characteristics such as contrast and haze of an image captured by an imaging device can be suppressed. The average particle diameter of the particulates is preferably 100 nm or less. In this case, the effect of Rayleigh scattering is reduced, so that the transparency to visible light is increased in the light absorbing film formed using the light absorbing composition. In addition, the average particle diameter of the particulates is more preferably 75 nm or less. In this case, the light-absorbing film produced using the light-absorbing composition has particularly high transparency to visible light. The average particle size of the fine particles can be measured by dynamic light scattering.

[0039] The light absorbing composition may further contain, for example, a phosphate ester. The function of the ter makes it easy for the light absorber to be appropriately dispersed in the light absorbing composition or the light absorbing film obtained by curing the same. In addition to functioning as a dispersant, the phosphate ester may react with a metal component to form a compound. The phosphate ester may further coordinate or react with a compound formed by a metal component and a phosphonic acid to form a compound. The light absorber may contain these compounds or copper salts thereof.

[0040] The phosphate ester is, for example, a phosphate ester having a polyoxyalkyl group. The phosphate ester having a polyoxyalkyl group is not limited to a specific phosphate ester. The phosphate ester having a polyoxyalkyl group is, for example, Plysurf A208N: polyoxyethylene alkyl (C12, C13) ether phosphate ester, Plysurf A208F: polyoxyethylene alkyl (C8) ether phosphate ester, Plysurf A208B: polyoxyethylene lauryl ether phosphate ester, Plysurf A219B: polyoxyethylene lauryl ether phosphate ester, Plysurf AL: polyoxyethylene styrenated phenyl ether phosphate ester, Plysurf A212C: polyoxyethylene tridecyl ether phosphate ester, or Plysurf A215C: polyoxyethylene tridecyl ether phosphate ester. All of these are products manufactured by Daiichi Kogyo Seiyaku Co., Ltd. The phosphate ester may also be, for example, NIKKOL DDP-2: polyoxyethylene alkyl ether phosphate ester, NIKKOL DDP-4: polyoxyethylene alkyl ether phosphate ester, or NIKKOL DDP-6: polyoxyethylene alkyl ether phosphate ester. These are all products manufactured by Nikko Chemicals Co., Ltd. In the light absorbing composition, the mass ratio of the content of phosphonic acid to the content of phosphoric ester is 0.2 to 10.0, and preferably 0.3 to 8.0.

[0041] The light absorbing composition may further contain a resin. The resin is preferably a transparent resin that exhibits high transmittance at least in the visible light range. For example, but not limited to, acrylic resin, epoxy resin, polycarbonate resin, polyether resin, polyester resin, cyclic olefin resin, silicone resin, etc. may be used as the resin.

[0042] The resin is preferably a silicone resin containing an aryl group such as a phenyl group. If the resin contained in the light absorbing film is hard (rigid), as the thickness of the layer containing the resin increases, cracks are likely to occur due to hardening shrinkage during the preparation of the light absorbing film. If the resin is a silicone resin containing an aryl group, the light absorbing film formed by the light absorbing composition is likely to have good crack resistance. In addition, silicone resins containing an aryl group tend to have high compatibility or dispersibility with phosphonic acid and ultraviolet absorbers, and are unlikely to cause the light absorber to aggregate. Specific examples of silicone resins include KR-255, KR-300, KR-2621-1, KR-211, KR-311, KR-216, KR-212, KR-251, and KR-5230. All of these are silicone resins manufactured by Shin-Etsu Chemical Co., Ltd.

[0043] In the light absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the solid content of the resin is not limited to a specific value. The ratio is, for example, 0.1% to 1.8% by mass, and preferably 0.2% to 1.5%. This is advantageous from the viewpoint of suppressing the occurrence of problems such as a decrease in weather resistance or bleed-out.

[0044] The light absorbing composition may further contain alkoxysilane as required. In this case, siloxane bond (-Si-O-Si-) is formed by hydrolysis and polycondensation of alkoxysilane, and the light absorbing film is likely to have a dense structure. The alkoxysilane may be a monomer, or may be in the form of an oligomer or polymer in which hydrolysis and polycondensation have progressed to a certain extent, or may be a mixture thereof.

[0045] Examples of the alkoxysilane monomer include tetraethoxysilane, tetramethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane, from the viewpoints of easy availability, easy reaction control, film adhesion, film weather resistance, etc. One or more types of alkoxysilanes can be used within the range that does not affect the effects of the present invention.

[0046] By including these alkoxysilanes in the light-absorbing composition, the aggregation of the light-absorbing agent composed of phosphonic acid and a metal component is inhibited, and the amount of the phosphate compound that functions as a dispersant added can be reduced.

[0047] An example of a method for preparing a light-absorbing composition will be described. A metal salt such as an acetate is added to a predetermined solvent such as tetrahydrofuran (THF) and stirred to prepare a solution A of the metal salt. In preparing the solution A, a phosphoric acid ester may be added. Next, a phosphonic acid is added to a predetermined solvent such as THF and stirred to prepare a solution B. When the light-absorbing composition contains a plurality of types of phosphonic acid, each phosphonic acid may be added to a predetermined solvent such as THF and stirred to prepare a plurality of spare solutions prepared for each type of phosphonic acid, and then the solution B may be prepared. In preparing the solution B, an alkoxysilane may be added as necessary. The phosphonic acid used in preparing the solution B is, for example, a phosphonic acid having an aryl group or a halogenated aryl group. While stirring the solution A, the solution B is added to the solution A and stirred for a predetermined time. Next, a predetermined solvent such as toluene is added to this solution and stirred to obtain a solution C. Next, the solution C is heated and subjected to a desolvation treatment for a predetermined time to obtain a solution D. As a result, the components generated by dissociation of the solvent such as THF and the metal salt such as acetic acid (boiling point: about 118°C) are removed, and the light absorber is generated by the phosphonic acid and the metal component. The temperature at which the liquid C is heated is determined based on the boiling point of the component to be removed that is dissociated from the metal salt. In the desolvation process, the solvent such as toluene (boiling point: about 110°C) used to obtain the liquid C also volatilizes. Since it is desirable that this solvent remains to some extent in the light absorbing composition, the amount of the solvent added and the time of the desolvation process can be determined from this viewpoint. In addition, o-xylene (boiling point: about 144°C) can be used instead of toluene to obtain the liquid C. In this case, since the boiling point of o-xylene is higher than that of toluene, the amount added can be reduced to about one-fourth of the amount added of toluene.

[0048] If necessary, the H liquid may be prepared as follows. A metal salt such as an acetate is added to a predetermined solvent such as THF and stirred to prepare an E liquid, which is a solution of the metal salt. In preparing the E liquid, a phosphoric acid ester may be added. Next, a phosphonic acid is added to a predetermined solvent such as THF and stirred to prepare an F liquid. The phosphonic acid used in preparing the F liquid may be, for example, a phosphonic acid having an alkyl group or a halogenated alkyl group. While stirring the E liquid, the F liquid is added to the E liquid and stirred for a predetermined time. Next, a predetermined solvent such as toluene is added to this solution and stirred to obtain a G liquid. Next, the G liquid is heated and subjected to a desolvation treatment for a predetermined time to obtain a H liquid. As a result, components generated by dissociation of the metal salt such as the solvent such as THF and acetic acid (boiling point: about 118°C) are removed, and a light absorber is generated by the phosphonic acid and the metal component. The temperature at which the G liquid is heated is determined based on the boiling point of the component to be removed that is dissociated from the metal salt. In addition, in the solvent removal process, the solvent such as toluene (boiling point: about 110°C) used to obtain the G liquid also volatilizes. Since it is desirable that this solvent remains to some extent in the light absorbing composition, the amount of solvent added and the time of the solvent removal process can be determined from this viewpoint. In addition, o-xylene (boiling point: about 144°C) can be used instead of toluene to obtain the G liquid. In this case, since the boiling point of o-xylene is higher than that of toluene, the amount added can be reduced to about one-fourth of the amount added of toluene.

[0049] An ultraviolet absorber having a hydroxyl group and a carbonyl group in the molecule is added to a specific solvent such as toluene and stirred to obtain U liquid. A light absorbing composition can be prepared by mixing and stirring U liquid and D liquid together with a silicone resin as necessary. A light absorbing composition can also be prepared by mixing and stirring U liquid, D liquid, and H liquid together with a silicone resin as necessary. U liquid may be added in the preparation of D liquid or H liquid. For example, U liquid may be added in the preparation of C liquid and G liquid.

[0050] The light-absorbing composition can be used to provide, for example, a light-absorbing film 10 as shown in FIG. 1. The light-absorbing film 10 can be obtained, for example, by curing a coating of the light-absorbing composition. The light-absorbing film 10 contains phosphonic acid, an ultraviolet absorber having a hydroxyl group and a carbonyl group in the molecule, and a metal component. This makes it easier for the light-absorbing film 10 to effectively absorb light in the short wavelength region around a wavelength of 400 nm.

[0051] In the ultraviolet absorber of the light absorbing film 10, the hydroxy group and the carbonyl group are preferably spaced apart by 1 to 6 atoms, which makes it easier for the light absorbing film 10 to more reliably absorb light with a wavelength of about 400 nm effectively and appropriately.

[0052] In the transmission spectrum of the light absorbing film 10 at an incident angle of 0 degrees, the transmittance T 400 , transmittance T at wavelength 550 nm 550 , and transmittance T at a wavelength of 800 nm 800 , 8≦T 550 / T 400 and 8≦T 550 / T 800 This satisfies the condition for light absorption. The coating 10 is likely to exhibit high transmittance for visible light while adequately absorbing ultraviolet and infrared rays in the wavelength range around the visible light range.

[0053] In the light absorbing film 10, the transmittance T 400 , transmittance T 550 , and transmittance T 800 is preferably 12≦T 550 / T 400 and 28≦T 550 / T 800 and more preferably 16≦T 550 / T 400 and 60≦T 550 / T 800 Meet the conditions.

[0054] The ultraviolet absorbent in the light absorbing film 10 contains, for example, a benzophenone-based compound represented by the above formula (A1). This makes it easier for the light absorbing film 10 to more reliably and effectively absorb light in the short wavelength region around 400 nm.

[0055] The ultraviolet absorber in the light absorbing film 10 preferably contains a benzophenone compound represented by the above formula (A2). This makes it easier for the light absorbing film 10 to more reliably absorb light in the short wavelength region around 400 nm effectively.

[0056] The phosphonic acid in the light absorbing film 10 is represented by, for example, the above formula (B). This allows the light absorbing film 10 to effectively absorb light in a wavelength region longer than 750 nm, and more reliably absorb light in a short wavelength region around 400 nm.

[0057] The metal component in the light absorbing film 10 is, for example, a copper component. In this case, the light absorbing film 10 is more likely to effectively absorb light in the short wavelength region around 400 nm.

[0058] The light absorbing film 10 may further contain, for example, a phosphate ester. The action of the phosphate ester makes it easier for the light absorbing agent to be appropriately dispersed in the light absorbing film 10.

[0059] 1, for example, an optical filter 1a can be provided that includes a light absorbing film 10. The optical filter 1a can easily effectively absorb light in the short wavelength region around 400 nm.

[0060] In the transmission spectrum of the optical filter 1a at an incident angle of 0 degrees, Transmittance T 400 , transmittance T at wavelength 550 nm 550 , and transmittance T at a wavelength of 800 nm 800 For example, 8≦T 550 / T 400 and 8≦T 550 / T 800 Meet the conditions.

[0061] In the optical filter 1a, the transmittance T 400 , transmittance T 550 , and transmittance T 800 is desirable For most cases, 12≦T 550 / T 400 and 28≦T 550 / T 800 and more preferably 16≦T 550 / T 400 and 60≦T 550 / T 800 In addition, in the optical filter 1a, the transmittance T 400 , transmittance T 550 , and transmittance T 800 For example, T 550 / T 400 ≦120 and T 550 / T 800 ≦1×10 7 and preferably T 550 / T 400 ≦100 and T 550 / T 800 ≦1×10 6 Meet the conditions.

[0062] In the transmission spectrum of the optical filter 1a at an incident angle of 0 degrees, it is preferable that the following conditions (I), (II), (III), (IV), (V), (VI), (VII), (VIII), (IX), and (X) are further satisfied, so that the optical filter 1a is likely to exhibit the desired characteristics. (I) Maximum transmittance T at wavelengths of 300 nm to 380 nm M 300-380 (II) The transmittance T at a wavelength of 400 nm is 1% or less. 400 is less than 20%. (III) UV cutoff wavelengths with a transmittance of 50% at wavelengths of 400 nm to 490 nm Toe-off wavelength λ UV CF 405 nm ≦ λ UV CF Meets the condition of ≦480nm. (IV) Average transmittance T at wavelengths of 480 nm to 580 nm A 480-580 is more than 78%. (V) IR cutoff wavelength λ, which is the wavelength at which the transmittance is 50% in the wavelength range of 590 nm to 700 nm IR CF , 600nm≦λ IR CF Meets the condition of ≦700nm. (VI) Average transmittance T at wavelengths of 700 nm to 750 nm A 700-750 is less than 10%. (VII) Maximum transmittance T at wavelengths from 800 nm to 950 nm M 800-950 is 3% or less . (VIII) Maximum transmittance T at wavelengths from 700 nm to 1000 nm M 700-1000 Less than 10% It is. (IX) Maximum transmittance T at wavelengths from 700 nm to 1100 nm M 700-1100 is less than 15% be. (X) Maximum transmittance T at wavelengths from 700 nm to 1200 nm M 700-1200 is less than 20% be.

[0063] Regarding the above condition (I), in the transmission spectrum of the optical filter 1a at an incident angle of 0 degrees, it is preferable that the maximum transmittance T M 300-385 is 1% or less, and more preferably, the maximum transmittance T M 300-390 is less than 1%.

[0064] Regarding the above condition (II), the transmittance T 400 is preferably 10% or less, and more preferably Or less than 5%.

[0065] Regarding the above condition (III), it is preferable that 405 nm≦λ UV CF ≦470nm condition is met More preferably, 405 nm≦λ UV CF The condition ≦460 nm is met.

[0066] Regarding the above condition (IV), the average value T A 480-580 is preferably 82% or more.

[0067] Regarding the above condition (V), it is preferable that 620 nm≦λ IR CF The condition ≦680 nm is met.

[0068] Regarding the above condition (VI), the average value T A 700-750 is preferably 3% or less.

[0069] Regarding the above condition (VII), the maximum transmittance T M 800-950 is preferably less than 1%. , and more desirably 0.5% or less.

[0070] Regarding the above condition (VIII), the maximum transmittance T M 700-1000 is preferably 7% or less. and more desirably, 5% or less.

[0071] Regarding the above condition (IX), the maximum transmittance T M 700-1100 is preferably 10% or less. and more desirably, 5% or less.

[0072] Regarding the above condition (X), the maximum transmittance T M 700-1200 is preferably 15% or less. and more desirably, 10% or less.

[0073] The transmission spectrum of the optical filter 1a at an incident angle of 0 degrees may satisfy, for example, the following conditions (α), (β), and (γ). (α) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 300 nm to 450 nm RUV 1% is 90 nm or more. (β) IR cutoff wavelength λ IR CF and UV cutoff wavelength λ UV CF Difference λ R CF is 180 nm That's all. (γ) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 700 nm to 1200 nm RIR 1% is 200 nm or more.

[0074] By satisfying condition (α), the optical filter 1a can exhibit good ultraviolet absorbing performance. By satisfying condition (β), a sufficient amount of visible light can be received by a sensor such as a solid-state imaging element that receives light that has passed through the optical filter 1a. By satisfying condition (γ), the optical filter 1a can exhibit good infrared absorbing performance. Therefore, by satisfying conditions (α), (β), and (γ), the optical filter 1a can exhibit good ultraviolet and ultraviolet absorbing performance, i.e., good UV-IR absorbing performance.

[0075] Regarding the condition of (γ), the difference λ RIR 1% is preferably 300 nm or more, and more preferably is greater than or equal to 350 nm.

[0076] The optical filter 1a is, for example, composed of a single light absorbing film 10. In this case, the optical filter 1a can be used, for example, separately from an imaging element or an optical component. The optical filter 1a may be bonded to the imaging element and the optical component. On the other hand, the optical filter 1a may be constructed by applying the above-mentioned light absorbing composition to the imaging element or the optical component and curing the light absorbing composition.

[0077] The thickness of the light absorbing film 10 is not limited to a specific value. The thickness of the light absorbing film 10 is, for example, 10 μm to 600 μm, may be 20 μm to 400 μm, or may be 30 μm to 300 μm.

[0078] The optical filter 1a can be produced, for example, by peeling off the light absorbing film 10 formed on a substrate from the substrate. In this case, the material of the substrate may be glass, resin, or metal. The surface of the substrate may be subjected to a surface treatment such as coating with a fluorine-containing compound.

[0079] The optical filter 1a may be modified, for example, to an optical filter 1b shown in FIG. 2. The optical filter 1b is configured similarly to the optical filter 1a, unless otherwise specified. The components of the optical filter 1b that are the same as or correspond to the components of the optical filter 1a are denoted by the same reference numerals, and detailed description thereof will be omitted. The description of the optical filter 1a also applies to the optical filter 1b as long as there is no technical contradiction.

[0080] 2, the optical filter 1b includes a light-absorbing film 10 and a transparent dielectric substrate 20. The light-absorbing film 10 is formed parallel to one of the main surfaces of the transparent dielectric substrate 20. The light-absorbing film 10 may be in contact with one of the main surfaces of the transparent dielectric substrate 20, for example. In this case, the light-absorbing film 10 can be formed, for example, by applying the above-mentioned light-absorbing composition to one of the main surfaces of the transparent dielectric substrate 20 and curing the light-absorbing composition.

[0081] The type of the transparent dielectric substrate 20 is not limited to a specific type. The transparent dielectric substrate 20 may have an absorption ability in the infrared region. The transparent dielectric substrate 20 may have an average spectral transmittance of 90% or more at wavelengths of, for example, 350 nm to 900 nm. The material of the transparent dielectric substrate 20 is not limited to a specific material, but may be, for example, a specific glass or resin. When the material of the transparent dielectric substrate 20 is glass, the transparent dielectric substrate 20 may be, for example, transparent glass made of silicate glass such as soda-lime glass and borosilicate glass, or phosphate glass and fluorophosphate glass containing coloring components such as Cu and Co. Phosphate glass and fluorophosphate glass containing coloring components are, for example, infrared absorbing glass, and have light absorbing properties themselves. When the light absorbing film 10 is used together with the transparent dielectric substrate 20 of infrared absorbing glass, the light absorbing properties and transmission spectrum of both can be adjusted to produce an optical filter having desired optical properties, and the degree of freedom in designing the optical filter is high.

[0082] When the material of the transparent dielectric substrate 20 is a resin, the resin is, for example, a cyclic olefin resin such as a norbornene resin, a polyarylate resin, an acrylic resin, a modified acrylic resin, a polyimide resin, a polyetherimide resin, a polysulfone resin, a polyethersulfone resin, a polycarbonate resin, or a silicone resin.

[0083] Each of the optical filters 1a and 1b may be modified to further include other functional films, such as an infrared reflecting film and an anti-reflection film. Such functional films may be formed on the light absorbing film 10 or the transparent dielectric substrate 20. For example, the optical filter may include an anti-reflection film to increase the transmittance in a predetermined wavelength range (e.g., the visible light range). The anti-reflection film may be configured as a layer of a low refractive index material such as MgF2 and SiO2, or may be configured as a laminate of such a layer of a low refractive index material and a layer of a high refractive index material such as TiO2. Such an anti-reflection film may be formed by a method involving a physical reaction, such as a vacuum deposition method or a sputtering method, or by a method involving a chemical reaction, such as a CVD method or a sol-gel method.

[0084] The optical filter may be configured, for example, with the light absorbing film 10 disposed between two sheets of glass in the form of plates. This improves the rigidity and mechanical strength of the optical filter. In addition, the main surface of the optical filter becomes hard, which is advantageous from the viewpoint of preventing scratches, etc. In particular, when a relatively flexible resin is used as the binder or matrix in the light absorbing film 10, such an advantage is important. EXAMPLES

[0085] The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0086] <Example 1> 4,500 g of copper acetate monohydrate and 240 g of tetrahydrofuran (THF) were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, a phosphate ester compound was added to the obtained copper acetate solution. A quantity of 1.646 g of Plysurf A208N (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), which is a phosphonic acid derivative, was added and stirred for 30 minutes to obtain liquid 1-A. 40 g of THF was added to 0.706 g of phenylphosphonic acid and stirred for 30 minutes to obtain liquid 1-B1. 40 g of THF was added to 4.230 g of 4-bromophenylphosphonic acid and stirred for 30 minutes to obtain liquid 1-B2. Next, liquids 1-B1 and 1-B2 were mixed and stirred for 1 minute, and 8.664 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) and 2.830 g of tetraethoxysilane (TEOS) (manufactured by Kishida Chemical Co., Ltd., special grade) were added to this mixture and stirred for another 1 minute to obtain liquid 1-B. The solution was stirred while adding the solution 1-B to the solution 1-A, and stirred at room temperature for 1 minute. Next, 140 g of toluene was added to this solution, and stirred at room temperature for 1 minute to obtain the solution 1-C. The solution 1-C was placed in a flask and heated in an oil bath (manufactured by Tokyo Rika Kikai Co., Ltd., model: OSB-2100), while performing a desolvation treatment using a rotary evaporator (manufactured by Tokyo Rika Kikai Co., Ltd., model: N-1110SF). The set temperature of the oil bath was adjusted to 105°C. Then, the solution after the desolvation treatment was taken out of the flask, and the solution 1-D was obtained. In this way, the solution 1-D containing an aryl phosphonic acid, a copper component, and a phosphoric acid ester was obtained.

[0087] The ultraviolet absorber Uvinul 3049 (BASF, 2,2'-dihydroxy-4, 0.12 g of 4'-dimethoxybenzophenone and 99.88 g of toluene were mixed and stirred for 30 minutes to obtain 1-U solution containing an ultraviolet absorber.

[0088] 4.500g of copper acetate monohydrate and 240g of THF were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 2.572g of Plysurf A208N, a phosphate ester compound, was added to the obtained copper acetate solution and stirred for 30 minutes to obtain solution 1-E. 40g of THF was added to 2.886g of n-butylphosphonic acid and stirred for 30 minutes to obtain solution 1-F. The 1-F solution was added while stirring, and the mixture was stirred at room temperature for 1 minute. Next, the 1-U solution containing an ultraviolet absorber was added to this solution, and the mixture was stirred at room temperature for 1 minute to obtain the 1-G solution. The 1-G solution was placed in a flask and heated in an oil bath, and the solvent was removed using a rotary evaporator. The temperature of the oil bath was adjusted to 105°C. The solution after the solvent removal treatment was then removed from the flask, and the 1-H solution was obtained. In this way, the 1-H solution containing an alkyl phosphonic acid, a copper component, a phosphoric acid ester, and an ultraviolet absorber was obtained.

[0089] 8.800 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to the 1-D liquid, and the mixture was stirred for 30 minutes to obtain the 1-I liquid. An amount equivalent to 40 mass % of the total amount of the 1-H liquid was added to the 1-I liquid, and the mixture was stirred for another 30 minutes to obtain the light-absorbing composition according to Example 1. The light-absorbing composition according to Example 1 contained an aryl-based phosphonic acid, an alkyl-based phosphonic acid, a copper component, a phosphoric acid ester, an alkoxysilane or a hydrolyzate thereof, a polymerizable resin (silicone resin), and an ultraviolet absorber. The content of each component of the light-absorbing composition according to Example 1 is shown in Table 1. In Table 1, the ratio of the content of the ultraviolet absorber to the content of the solid content of the resin was calculated on the assumption that the content of the solid content of the resin was 50% by mass.

[0090] The light absorbing composition according to Example 1 was applied to a 40 mm x 40 mm area in the center of one main surface of a transparent glass substrate (manufactured by SCHOTT, product name: D263 T eco) made of borosilicate glass having dimensions of 76 mm x 76 mm x 0.21 mm using a dispenser to form a coating film. The obtained coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45°C for 2 hours and at 85°C for 30 minutes to volatilize the solvent and harden the coating film. Furthermore, the transparent glass substrate was placed in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this way, the light absorbing film according to Example 1 was formed, and the optical filter according to Example 1 was obtained.

[0091] (Transmission spectrum measurement) The transmission spectrum of the optical filter according to Example 1 at an incident angle of 0° was measured using an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The transmission spectrum of the optical filter according to Example 1 is shown in FIG. 3. The characteristics related to the transmittance read from FIG. 3 are shown in Tables 2, 3, and 4. From these results, it was confirmed that the transmittance at 400 nm of the optical filter according to Example 1 was 5% or less, and that the optical filter according to Example 1 has desirable absorption characteristics for light in the short wavelength region including ultraviolet light and has good optical characteristics. For reference, the transmission spectrum of D263 T eco used as a transparent glass substrate is shown in FIG. 11.

[0092] (Thickness measurement) The thickness of the light absorbing film was calculated by measuring the distance from the surface of the optical filter using a laser displacement meter (Keyence Corporation, product name: LK-H008) and subtracting the thickness of the transparent glass substrate. The results are shown in Table 2.

[0093] <Example 2> A light-absorbing composition according to Example 2 was prepared in the same manner as in Example 1, except that a 2-U solution containing an ultraviolet absorber prepared by mixing 0.04 g of Uvinul3049 (manufactured by BASF) and 99.96 g of toluene was used instead of the 1-U solution used in the preparation of the light-absorbing composition according to Example 1, and a light-absorbing film was formed to produce an optical filter according to Example 2. The transmission spectrum of the optical filter according to Example 2 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light-absorbing film in the optical filter according to Example 2 was calculated in the same manner as in Example 1. The transmission spectrum of the optical filter according to Example 2 at an incident angle of 0° is shown in FIG. 4. The parameters and the film thickness of the light-absorbing film that can be seen from the transmission spectrum in FIG. 4 are shown in Tables 2 to 4. From these results, it was confirmed that the transmittance at 400 nm of the optical filter according to Example 2 was 5% or less, and the optical filter according to Example 2 had desirable absorption performance for light in the short wavelength region including ultraviolet light, and had good optical properties.

[0094] <Example 3> 4.500g of copper acetate monohydrate was mixed with 240g of tetrahydrofuran (THF) and stirred for 3 hours to obtain a copper acetate solution. Next, 1.646g of Plysurf A208N, a phosphate ester compound, was added to the copper acetate solution and stirred for 30 minutes to obtain solution 3-A. 40g of THF was added to 0.706g of phenylphosphonic acid and stirred for 30 minutes to obtain solution 3-B1. 4.230g of 4-bromophenylphosphonic acid was added to 40g of THF and stirred for 30 minutes to obtain solution 3-B2. Next, 3-B1 liquid and 3-B2 liquid were mixed and stirred for 1 minute, and 8.664 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) and 2.830 g of tetraethoxysilane (TEOS) (manufactured by Kishida Chemical Co., Ltd., special grade) were added to this mixed liquid and stirred for another 1 minute to obtain 3-B liquid. 3-A liquid was added to 3-B liquid while stirring, and stirred for 1 minute at room temperature. Next, 140 g of toluene was added to this solution, and stirred for 1 minute at room temperature to obtain 3-C liquid. 3-C liquid was placed in a flask and heated in an oil bath (manufactured by Tokyo Rikakikai Co., Ltd., model: OSB-2100), while performing a solvent removal treatment using a rotary evaporator (manufactured by Tokyo Rikakikai Co., Ltd., model: N-1110SF). The set temperature of the oil bath was adjusted to 105°C. The solution after the solvent removal treatment was then removed from the flask to obtain the 3-D solution, which contained the aryl phosphonic acid, the copper component, and the phosphate ester.

[0095] 5 g of an ultraviolet absorbent, Uvinul 3050 (manufactured by BASF, 2,2',4,4'-tetrahydroxybenzophenone), and 95 g of ethanol were mixed and stirred for 30 minutes to obtain 3-U solution containing the ultraviolet absorbent.

[0096] 4,500 g of copper acetate monohydrate and 240 g of THF were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 2.572 g of Plysurf A208N, a phosphate ester compound, was added to the copper acetate solution and stirred for 30 minutes to obtain solution 3-E. 40 g of THF was added to 2.886 g of n-butylphosphonic acid and stirred for 30 minutes to obtain solution 3-F. Solution 3-E While stirring, 3-F solution was added to 3-E solution, and stirred at room temperature for 1 minute. Next, 100 g of toluene was added to this solution, and stirred at room temperature for 1 minute to obtain 3-G solution. 3-G solution was placed in a flask and heated in an oil bath, and a solvent removal treatment was performed using a rotary evaporator. The temperature of the oil bath was adjusted to 105°C. After that, 3-H solution after the solvent removal treatment was taken out of the flask, and 3-H solution was obtained. In this way, 3-H solution containing an alkyl phosphonic acid, a copper component, and a phosphoric acid ester was obtained.

[0097] 8.800 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to the 3-D liquid, and the mixture was stirred for 30 minutes to obtain a 3-I liquid. An amount equivalent to 40 mass % of the total amount of the 3-H liquid was added to the 3-I liquid, and 0.96 g of the 3-U liquid containing an ultraviolet absorber was further added and stirred for 30 minutes to obtain a light absorbing composition according to Example 3. The light absorbing composition according to Example 3 contained an aryl phosphonic acid, an alkyl phosphonic acid, a copper component, a phosphoric acid ester, an alkoxysilane or a hydrolyzate thereof, a polymerizable resin (silicone resin), and an ultraviolet absorber.

[0098] The light absorbing composition according to Example 3 was applied to a 40 mm×40 mm area in the center of one of the main surfaces of a transparent glass substrate (manufactured by SCHOTT, product name: D263 T eco) made of borosilicate glass having dimensions of 76 mm×76 mm×0.21 mm using a dispenser to form a coating film. The obtained coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45° C. for 2 hours and at 85° C. for 30 minutes to volatilize the solvent and harden the coating film. Furthermore, the transparent glass substrate was placed in an environment of a temperature of 85° C. and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this way, the light absorbing film according to Example 3 was formed, and the optical filter according to Example 3 was obtained. The transmission spectrum of the optical filter according to Example 3 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light absorbing film in the optical filter according to Example 3 was calculated in the same manner as in Example 1. The transmission spectrum of the optical filter according to Example 3 at an incident angle of 0° is shown in FIG. 5. The parameters and the thickness of the light absorbing film that can be seen from the transmission spectrum in Fig. 5 are shown in Tables 2 to 4. From these results, it was confirmed that the transmittance at 400 nm of the optical filter according to Example 3 is 5% or less, and the optical filter according to Example 3 has desirable absorption performance for light in the short wavelength region including ultraviolet light, and has good optical characteristics.

[0099] <Example 4> A light-absorbing composition according to Example 4 was prepared in the same manner as in Example 3, except that a 4-U solution containing an ultraviolet absorber prepared by mixing 1.67 g of Uvinul 3050 (manufactured by BASF) and 98.33 g of toluene was used instead of the 3-U solution used in the preparation of the light-absorbing composition according to Example 3, and a light-absorbing film was formed to produce an optical filter according to Example 4. The transmission spectrum of the optical filter according to Example 4 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light-absorbing film in the optical filter according to Example 4 was calculated in the same manner as in Example 1. The transmission spectrum of the optical filter according to Example 4 at an incident angle of 0° is shown in FIG. 6. The parameters and the film thickness of the light-absorbing film that can be seen from the transmission spectrum in FIG. 6 are shown in Tables 2 to 4. From these results, it was confirmed that the transmittance at 400 nm of the optical filter according to Example 4 was 5% or less, and the optical filter according to Example 4 had desirable absorption performance for light in the short wavelength region including ultraviolet light, and had good optical properties.

[0100] <Comparative Example 1> 0.250 g of an ultraviolet absorbent, Uvinul 3049 (manufactured by BASF), and 12.25 g of toluene were mixed and stirred for 30 minutes to dissolve the ultraviolet absorbent. To the solution, 25,000 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added, and the solution was stirred for 30 minutes, thereby obtaining an ultraviolet absorbing composition according to Comparative Example 1.

[0101] The ultraviolet absorbing composition according to Comparative Example 1 was applied to a 40 mm x 40 mm area in the center of one main surface of a transparent glass substrate (manufactured by SCHOTT, product name: D263 T eco) made of borosilicate glass having dimensions of 76 mm x 76 mm x 0.21 mm using a dispenser to form a coating film. The resulting coating film was placed in an oven and heat-treated at 45°C for 2 hours and at 85°C for 1 hour to volatilize the solvent and harden the coating film. In this way, the light absorbing film according to Comparative Example 1 was formed, and the ultraviolet absorbing filter according to Comparative Example 1 was obtained.

[0102] The transmission spectrum of the ultraviolet absorption filter according to Comparative Example 1 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light absorbing film in the ultraviolet absorption filter according to Comparative Example 1 was calculated in the same manner as in Example 1. The transmission spectrum of the ultraviolet absorption filter according to Comparative Example 1 at an incident angle of 0° is shown in FIG. 7. The parameters and the film thickness of the light absorbing film that can be seen from the transmission spectrum in FIG. 7 are shown in Tables 2 to 4. From these results, it was found that the ultraviolet absorption filter according to Comparative Example 1 has a high transmittance of 40.78% at a wavelength of 400 nm, and has a problem with absorbing light at a wavelength of around 400 nm. This is due to the absorption characteristics of the dye of Uvinul3049, and it was confirmed that Uvinul3049 alone cannot sufficiently absorb light at around 400 nm.

[0103] <Comparative Example 2> Except for using Uvinul3050 (manufactured by BASF) instead of the ultraviolet absorbent used in the preparation of the ultraviolet absorbing composition of Comparative Example 1, an ultraviolet absorbing composition of Comparative Example 2 was prepared in the same manner as in Comparative Example 1, and a light absorbing film was formed to produce an ultraviolet absorbing filter of Comparative Example 2. The transmission spectrum of the ultraviolet absorbing filter of Comparative Example 2 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light absorbing film in the ultraviolet absorbing filter of Comparative Example 2 was calculated in the same manner as in Example 1. The transmission spectrum of the ultraviolet absorbing filter of Comparative Example 2 at an incident angle of 0° is shown in FIG. 8. Each parameter and the film thickness of the light absorbing film that can be seen from the transmission spectrum of FIG. 8 are shown in Tables 2 to 4.

[0104] <Comparative Example 3> 4.500g of copper acetate monohydrate and 240g of tetrahydrofuran (THF) were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 1.646g of Plysurf A208N (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), a phosphate ester compound, was added to the obtained copper acetate solution and stirred for 30 minutes to obtain solution 13-A. 40g of THF was added to 0.706g of phenylphosphonic acid and stirred for 30 minutes to obtain solution 13-B1. 4.230g of 4-bromophenylphosphonic acid was added to 40g of THF and stirred for 30 minutes to obtain solution 13-B2. Mix 13-B1 and 13-B2 solutions and stir for 1 minute. Then add 8.664 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) and 2.830 g of tetraethoxysilane (TEOS) (manufactured by Kishida Chemical Co., Ltd., special grade) to this mixture and stir for another 1 minute to obtain 13-B solution. The 13-B solution was added to the 13-A solution while stirring the 13-A solution, and the mixture was stirred at room temperature for 1 minute. Next, 140 g of toluene was added to the solution, and the mixture was stirred at room temperature for 1 minute to obtain the 13-C solution. The 13-C solution was placed in a flask and heated in an oil bath (manufactured by Tokyo Rika Kikai Co., Ltd., model: OSB-2100), while the solvent was removed using a rotary evaporator (manufactured by Tokyo Rika Kikai Co., Ltd., model: N-1110SF). The set temperature of the oil bath was adjusted to 105°C. The liquid after the solvent removal treatment was then taken out of the flask, and the 13-D solution was obtained. In this way, the 13-D solution containing an aryl phosphonic acid, a copper component, a phosphoric acid ester, and an alkoxysilane or a hydrolyzate thereof was obtained.

[0105] Copper acetate monohydrate (4,500 g) and THF (240 g) were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 2.572 g of Plysurf A208N, a phosphate ester compound, was added to the copper acetate solution and stirred for 30 minutes to obtain solution 13-E. Also, 40 g of THF was added to 2.886 g of n-butylphosphonic acid and stirred for 30 minutes to obtain solution 13-F. While stirring the 13-E solution, the 13-F solution was added to the 13-E solution, and the mixture was stirred at room temperature for 1 minute. Next, 100 g of toluene was added to the solution, and the mixture was stirred at room temperature for 1 minute to obtain the 13-G solution. The 13-G solution was placed in a flask and heated in an oil bath, and the solvent was removed using a rotary evaporator. The temperature of the oil bath was adjusted to 105°C. The solution after the solvent removal treatment was then removed from the flask, and the 13-H solution was obtained. In this manner, the 13-H solution containing an alkyl phosphonic acid, a copper component, and a phosphoric acid ester was obtained.

[0106] 8,800 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to the 13-D solution and stirred for 30 minutes to obtain the 13-I solution. An amount equivalent to 40 mass % of the total amount of the 13-H solution was added to the 13-I solution and stirred for 30 minutes to obtain the light absorbing composition according to Comparative Example 3. The light absorbing composition according to Comparative Example 3 contained an aryl-based phosphonic acid, an alkyl-based phosphonic acid, a copper component, a phosphoric acid ester, an alkoxysilane or a hydrolyzate thereof, and a polymerizable resin.

[0107] The light absorbing composition according to Comparative Example 3 was applied to a 40 mm x 40 mm area at the center of one main surface of a transparent glass substrate (manufactured by SCHOTT, product name: D263 T eco) made of borosilicate glass having dimensions of 76 mm x 76 mm x 0.21 mm using a dispenser to form a coating film. The obtained coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45°C for 2 hours and at 85°C for 30 minutes to volatilize the solvent and harden the coating film. Furthermore, the transparent glass substrate was placed in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this way, a light absorbing film according to Comparative Example 3 was formed, and an optical filter according to Comparative Example 3 was obtained.

[0108] The transmission spectrum of the optical filter according to Comparative Example 3 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light absorbing film in the optical filter according to Comparative Example 3 was calculated in the same manner as in Example 1. The transmission spectrum of the optical filter according to Comparative Example 3 at an incident angle of 0° is shown in FIG. 9. The parameters and film thicknesses of the light absorbing films that can be seen from the transmission spectrum in FIG. 9 are shown in Tables 2 to 4. From these results, it was confirmed that the transmittance at 400 nm of the optical filter according to Comparative Example 3 was 35.06%, and the ultraviolet absorbing characteristics of the optical filter according to Comparative Example 3 were insufficient.

[0109] <Comparative Example 4> A coating film was formed by applying the ultraviolet absorbing composition according to Comparative Example 1 to a 40 mm×40 mm area in the center of one main surface of a transparent glass substrate (manufactured by SCHOTT, product name: D263 T eco) made of borosilicate glass having dimensions of 76 mm×76 mm×0.21 mm using a dispenser. The obtained coating film was placed in an oven and heat-treated at 45° C. for 2 hours and at 85° C. for 1 hour, the solvent was volatilized, the coating film was hardened, and a light-absorbing film was formed. Next, a coating film was formed by applying the light-absorbing composition according to Comparative Example 3 to the other main surface of the transparent glass substrate in the same manner. The obtained coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45° C. for 2 hours and at 85° C. for 30 minutes, the solvent was volatilized, and the coating film was hardened. Thereafter, the transparent glass substrate was placed in an environment of a temperature of 85° C. and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this manner, a light-absorbing film according to Comparative Example 4 was formed on both sides of the transparent glass substrate, and an optical filter according to Comparative Example 4 was obtained.

[0110] The transmission spectrum of the optical filter according to Comparative Example 4 at an incident angle of 0° was measured in the same manner as in Example 1. In addition, the thickness of the light absorbing film in the optical filter according to Comparative Example 4 was calculated in the same manner as in Example 1. The transmittance of the optical filter according to Comparative Example 4 at an incident angle of 0° is shown in FIG. 0. Tables 2 to 4 show the parameters and the thickness of the light absorbing film that can be seen from the transmission spectrum. From these results, the transmittance of the optical filter according to Comparative Example 4 at a wavelength of 400 nm is as large as 14.52%, and it is difficult to say that the optical filter according to Comparative Example 4 has sufficient light absorption properties. Therefore, it was found that there is a problem with absorbing light at a wavelength of around 400 nm by simply forming a layer containing an ultraviolet absorber and a layer containing copper phosphonate separately and stacking them. Therefore, it is suggested that combining a predetermined ultraviolet absorber and a metal component in the same layer as in Examples 1 to 4 is advantageous in terms of absorbing light at a wavelength of around 400 nm.

[0111] UV cutoff wavelength λ of the optical filters according to Examples 1 to 4 UV CF are 445 nm, 434 nm, 436 nm, and 430 nm, respectively. In addition, the transmittance T 400 are 1.49%, 4.93%, 1.82%, and 4. On the other hand, the ultraviolet absorbing filters according to Comparative Examples 1 and 2 are filters that utilize the light absorption performance of a single benzophenone-based ultraviolet absorbent, and the UV cutoff wavelength λ of the ultraviolet absorbing filters according to Comparative Examples 1 and 2 is 54%. UV CF are 402 nm and 398 nm, respectively. In addition, the transmittance T 400 are 40 respectively. .78% and 57.15%. The optical filter according to Comparative Example 4 has a light absorbing film containing only a benzophenone-based ultraviolet absorber on both sides of a transparent glass substrate, and a light absorbing film containing phosphonic acid and a copper component. The UV cutoff wavelength λ of the optical filter according to Comparative Example 4 UV CF The transmittance T 400 teeth , 14.52%. Therefore, the UV cutoff wavelength λ of the optical filter according to the embodiment UV CFis the UV cutoff wavelength λ of the ultraviolet absorbing filters according to Comparative Examples 1 and 2 UV CF and the UV cutoff wavelength λ of the optical filter according to Comparative Example 4 is about 30 nm larger than that of the UV CF The transmittance T 400 Comparative Examples 1 and 2 The transmittance T400 of the optical filter according to Comparative Example 4 is about 35 points or more smaller than that of the optical filter according to Comparative Example 4. 400 From these results, the optical It is understood that the light absorption characteristics of the optical filter in the short wavelength region including ultraviolet rays can be expressed on the longer wavelength side than the light absorption characteristics exhibited by the benzophenone-based ultraviolet absorber alone. The mechanism for such an effect is unclear. For example, in the preparation process of the light absorbing composition, the hydroxyl group of the ultraviolet absorber interacts with the copper component to form a complex, which shifts the absorption characteristics inherent to the ultraviolet absorber to the longer wavelength side, resulting in such an effect.

[0112] According to Examples 1 to 4, it was found that in the light-absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the solid content of the resin is advantageous to obtain good characteristics when it is 0.36% to 1.09% by mass. On the other hand, according to Comparative Examples 1 and 2, in the ultraviolet-absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the solid content of the resin is 2.00% by mass, and a large amount of dye is added to the resin. Nevertheless, the ultraviolet absorption characteristics of the ultraviolet absorbing filters according to Comparative Examples 1 and 2 are significantly inferior to the ultraviolet absorption characteristics of the optical filters according to Examples 1 to 4. According to the present invention, it is understood that good ultraviolet absorption characteristics can be realized even if the ratio of the content of the ultraviolet absorber to the content of the solid content of the resin is adjusted to less than 2.00% in the light-absorbing composition. A small ratio of the content of the ultraviolet absorber to the content of the solid content of the resin is advantageous from the viewpoint of suppressing the occurrence of problems such as a decrease in weather resistance or bleed-out. In the light absorbing composition, the ratio of the content of the ultraviolet absorbing agent to the content of the solid content of the resin is preferably 0.1% to 1.8%, and more preferably 0.2% to 1.5%, on a mass basis.

[0113] According to Examples 1 to 4, in the light absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the phosphonic acid is adjusted to 0.263% to 0.788% by mass. From these results, it is clear that an optical filter can be effectively obtained by using a very small amount of the ultraviolet absorber compared to the phosphonic acid. It is understood that the composition can exhibit advantageous properties. When the ratio of the content of the ultraviolet absorber to the content of the phosphonic acid is not too large, the decrease in the transmittance of visible light can be suppressed. The ratio of the content of the ultraviolet absorber to the content of the phosphonic acid is preferably 0.1 to 5.0%, more preferably 0.1 to 3.0%, and even more preferably 0.1 to 1.0%, by mass.

[0114] According to Examples 1 to 4, in the light absorbing composition, the ratio of the content of the ultraviolet absorber to the content of the copper component is 0.002 to 0.006 on a substance basis. It is presumed that most of the copper component forms a complex with phosphonic acid. Therefore, the content of the copper component is larger than the content of the ultraviolet absorber. The ratio of the content of the ultraviolet absorber to the content of the copper component is preferably 0.001 to 0.100, more preferably 0.001 to 0.030 on a substance basis.

[0115] The optical filter of the present invention may be a laminate of a transparent substrate and a light absorbing film, which is prepared by applying a light absorbing composition onto a transparent glass substrate and curing the coating to form an absorbing film, as in the optical filters according to Examples 1 to 4. On the other hand, the optical filter of the present invention may be an optical filter consisting of only a light absorbing film, which is obtained by forming a light absorbing film on a support and then peeling the light absorbing film from the support. According to FIG. 11, it can be understood that the transmission spectrum of the transparent glass substrate does not greatly affect the optical properties shown in Tables 2 to 4. This is because, in the transmission spectrum of the transparent glass substrate, the transmittance is approximately constant at least from a specific wavelength exceeding 350 nm to a wavelength of 1200 nm. Therefore, even an optical filter including a light absorbing film and not including a transparent glass substrate can have a transmittance of 8≦T 550 / T 400 and 8≦T 550 / T 800 The conditions (I) to (X), and the conditions (α) to (γ) can be satisfied.

[0116] (Detection of ultraviolet absorbers) The ultraviolet absorbing agent contained in the light absorbing film was subjected to an ethanol elution test in the following manner.

[0117] <Example 5> First, in order to easily remove the light absorbing film from the optical filter, the main surface of the transparent glass substrate on which the light absorbing film is to be formed was previously surface-treated with a fluorine compound to prepare a fluorine-treated substrate. 0.1 g of a surface antifouling coating agent (manufactured by Daikin Industries, product name: Optool DSX, concentration of active ingredient: 20% by mass) and 19.9 g of a hydrofluoroether-containing liquid (manufactured by 3M, product name: Novec 7100) were mixed and stirred for 5 minutes to prepare a fluorine treatment agent (concentration of active ingredient: 0.1% by mass). This fluorine treatment agent was applied to the main surface of a transparent glass substrate made of borosilicate glass (manufactured by SCHOTT, product name: D263 T eco) measuring 76 mm x 76 mm x 0.21 mm to form a coating film, and the coating film of the fluorine treatment agent was left at room temperature for 24 hours to dry. Thereafter, the glass surface was lightly wiped with a dust-free cloth containing Novec 7100 to remove excess fluorine treatment agent, etc., to obtain a fluorine-treated substrate.

[0118] The entire amount of the light absorbing composition obtained under the same conditions and method as in Example 3 was applied to one main surface of a fluorine-treated substrate using a dispenser to form a coating film, and the obtained coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45°C for 2 hours and at 85°C for 30 minutes. This caused the solvent contained in the light absorbing composition to volatilize and the coating film to harden. Furthermore, the fluorine-treated substrate was placed in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this way, the light absorbing film according to Example 5 was formed, and the optical filter according to Example 5 was obtained. The ultraviolet absorber contained in the light absorbing film was 2,2'-4,4'-tetrahydroxybenzophenone.

[0119] Next, the light absorbing film was carefully peeled off from the optical filter according to Example 5 with tweezers to obtain a film-like light absorbing film. The mass of the light absorbing film according to Example 3 was 9,500 g. In the process of preparing the light-absorbing composition, the 3-U solution contained 5% by mass of the ultraviolet absorber, and the light-absorbing composition was prepared by adding 0.960 g of the 3-U solution, so the light-absorbing film contained 0.048 g of the ultraviolet absorber. The content of the ultraviolet absorber in the light-absorbing film was 0.505% by mass.

[0120] A part of the light-absorbing film was cut to take out a 0.100g fragment of the light-absorbing film, which was then immersed in 1.000g of ethanol for 24 hours to try to dissolve the ultraviolet absorber contained in the fragment of the light-absorbing film. The amount of ultraviolet absorber contained in the 0.100g fragment of the light-absorbing film was 0.000505g. Assuming that all of the ultraviolet absorber contained in this fragment was dissolved in ethanol, the amount of ultraviolet absorber in ethanol can be calculated to be 0.050% by mass. On the other hand, a fragment of the light-absorbing film was similarly prepared using the light-absorbing composition according to Comparative Example 3, which does not contain an ultraviolet absorber, as a control, and the fragment was immersed in 1.000g of ethanol for 24 hours to observe the state of dissolution.

[0121] The ethanol containing the fragments of the light-absorbing film containing the ultraviolet absorber was colored yellow, suggesting that a component having absorption in the region including the visible light region was eluted from the light-absorbing film into the ethanol. The ethanol containing the fragments of the light-absorbing film not containing the ultraviolet absorber remained almost colorless and transparent. In order to identify the component having absorption in the region including the visible light region in the ethanol containing the fragments of the light-absorbing film containing the ultraviolet absorber, LC-UV measurement was performed. For this measurement, a high-performance liquid chromatograph Ultimate3000 manufactured by Thermo Fisher Scientific was used. The spectrum of the LC-UV chromatograph in this measurement at a wavelength of 450±150 nm is shown in FIG. 12. In FIG. 12, the horizontal axis indicates time [min], and the vertical axis indicates relative absorption intensity. In addition, as a control, in the LC-UV chromatograph when only ethanol was used as a sample and the chromatograph spectrum when ethanol containing fragments of the light-absorbing film not containing the ultraviolet absorber was used as a sample, the background state (relative absorption intensity is almost zero) continued, and no characteristic movement was observed.

[0122] In Figure 12, a characteristic absorption intensity peak was observed at 5.8 minutes. The absorption spectrum of this peak is shown in Figure 13. The horizontal axis indicates wavelength [nm], and the vertical axis indicates relative absorbance. From the spectrum shown in Figure 13, it was confirmed that there were characteristic absorption peaks at wavelengths of 285 nm and 342 nm.

[0123] Next, LC-MS measurements were performed on ethanol containing fragments of the light-absorbing film containing the UV absorber. The measurements were performed using a Thermo Fisher Scientific liquid chromatography mass spectrometer, Orbitrap Fusion. According to the mass spectrum obtained as a result of the measurements, the elution into ethanol included C 13 H9O5 (negative ion detection) and C 13 H 11 It was found to contain O5 (positive ion detected).

[0124] From the results of these LC-UV and LC-MS measurements, it was estimated that the components eluted into ethanol from the light-absorbing film containing an ultraviolet absorber included the ultraviolet absorber tetrahydroxybenzophenone.

[0125] (Identification of eluted components of ultraviolet absorbers) The transmission spectrum of the ethanol solution in which the ultraviolet absorbent was dissolved from the fragments of the light absorbing film according to Example 5 was measured. The ethanol solution in which the ultraviolet absorbent was dissolved was filled in a quartz cell (manufactured by JASCO Corporation: model number J / 1 / Q / 1) with an optical path length of 1 mm, and the transmission spectrum was measured using an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The transmission spectrum is shown in FIG. 14. At wavelengths of 300 to 450 nm, the minimum transmittance divided by the maximum transmittance was 0.895. The minimum transmittance corresponded to the minimum transmittance at a wavelength of around 348 nm.

[0126] Next, 2,2',4,4'-tetrahydroxybenzophenone, an ultraviolet absorber, was dissolved in ethanol to prepare five kinds of ethanol solutions in which the ultraviolet absorber was dissolved at 0.005%, 0.010%, 0.025%, 0.100%, and 0.200% by mass. The transmission spectra of the ethanol solutions in which these ultraviolet absorbers were dissolved were measured in the same manner as the ethanol solutions in which the ultraviolet absorber was dissolved from the fragments of the light absorbing film containing the ultraviolet absorber according to Example 5. The transmission spectra are shown in FIG. 15. In these transmission spectra, the wavelength corresponding to the minimum value of the transmittance was 348 nm. Furthermore, in these transmission spectra, the value tr was obtained by dividing the minimum value of the transmittance by the maximum value of the transmittance. Table 5 and FIG. 16 show the relationship between the concentration η [%] of the ultraviolet absorber and the value tr. From the graph shown in FIG. 16, the relationship between the concentration η [%] and the value tr is expressed as η = (-1 / a) ln (tr / b) (where a = 1.213 × 10 1 , b=1.004). The dashed line in FIG. 16 shows the ultraviolet absorption 1 is a calibration curve for determining the concentration of the ultraviolet absorber. In the ethanol solution in which the ultraviolet absorber in the light-absorbing film according to Example 5 was dissolved, tr=0.895. Therefore, it was suggested that when the light-absorbing film according to Example 5 was immersed in ethanol and the ultraviolet absorber was dissolved in ethanol, the light-absorbing film had light transmission characteristics equivalent to those of an ethanol solution in which the ultraviolet absorber was dissolved so that the concentration of the ultraviolet absorber was 0.0095% by mass.

[0127] When the ultraviolet absorber is dissolved into ethanol from the fragment of the light-absorbing film containing the ultraviolet absorber according to Example 5, it is assumed that the ultraviolet absorber is contained in ethanol at 0.0095% by mass. It is understood from the above consideration that when all the ultraviolet absorber contained in the light-absorbing film is dissolved, the concentration of the ultraviolet absorber in the ethanol solution is 0.05%. Therefore, it is estimated that 19% by mass of the ultraviolet absorber contained in the light-absorbing film is dissolved into ethanol from the fragment of the light-absorbing film containing the ultraviolet absorber according to Example 5.

[0128] <Comparative Example 5> A light-absorbing composition according to Comparative Example 5 was obtained under the same conditions and by the same method as in Example 5, except that the addition of all phosphonic acid and copper acetate monohydrate was omitted. In addition, a fluorine-treated substrate was produced in the same manner as in Example 5. The entire amount of the light-absorbing composition according to Comparative Example 5 was applied to one main surface of a fluorine-treated substrate using a dispenser, and the resulting coating film was thoroughly dried at room temperature, and then placed in an oven and heat-treated at 45°C for 2 hours and at 85°C for 30 minutes to volatilize the solvent and harden the coating film. Furthermore, the transparent glass substrate was placed in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane. In this way, a light-absorbing film according to Comparative Example 5 was formed, and an optical filter according to Comparative Example 5 was obtained.

[0129] Next, the light absorbing film was carefully peeled off from the optical filter according to Comparative Example 5 with tweezers to obtain a film-like light absorbing film. The total amount of the obtained light absorbing film was 4.200 g. In the process of preparing the light absorbing composition according to Comparative Example 5, the liquid containing the ultraviolet absorber corresponding to the 3-U liquid contained 5 mass % of the ultraviolet absorber, and 0.960 g of the liquid was added to prepare the light absorbing composition. Therefore, the light absorbing film contained 0.048 g of the ultraviolet absorber, and the content of the ultraviolet absorber in the light absorbing film was 1.130% by mass.

[0130] A part of the light-absorbing film was cut, and a 0.100g fragment of the light-absorbing film was taken out and immersed in 1.000g of ethanol for 24 hours to attempt to elute the ultraviolet absorber contained in the fragment of the light-absorbing film. The amount of ultraviolet absorber contained in the 0.100g light-absorbing film was 0.00113g. Assuming that all of the ultraviolet absorber was dissolved in the ethanol, the concentration of the ultraviolet absorber in the ethanol solution can be calculated to be 0.113% by mass.

[0131] (Identification of eluted components of ultraviolet absorbers) The transmission spectrum was measured for the ethanol solution in which the ultraviolet absorbent was dissolved from the fragment of the light-absorbing film according to Comparative Example 5. The ethanol solution in which the ultraviolet absorbent was dissolved was The light was filled into a quartz cell (manufactured by JASCO Corporation: model number J / 1 / Q / 1) of 1 mm, and the transmission spectrum was measured using an ultraviolet-visible near-infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The transmission spectrum is shown in FIG. 17. At wavelengths of 300 to 450 nm, the value tr obtained by dividing the minimum transmittance by the maximum transmittance was 0.550. According to the calibration curve shown in FIG. 16 and the above formula representing the calibration curve, it was found that when the light-absorbing film according to Comparative Example 5 was immersed in ethanol to elute the ultraviolet absorbent into ethanol, the light-absorbing film had light transmission characteristics equivalent to those of an ethanol solution in which the ultraviolet absorbent was dissolved so that the concentration of the ultraviolet absorbent was 0.0496% by mass.

[0132] When the ultraviolet absorber is dissolved in ethanol from the fragment of the light-absorbing film containing the ultraviolet absorber according to Comparative Example 5, it is assumed that the ethanol solution contains 0.0496% ultraviolet absorber by mass. It is understood from the above consideration that when all the ultraviolet absorber contained in the light-absorbing film is dissolved in ethanol, the concentration of the ultraviolet absorber in the ethanol solution is 0.113%. Therefore, it is estimated that 43.89% of the ultraviolet absorber contained in the light-absorbing film is dissolved in ethanol.

[0133] Comparing Example 5 with Comparative Example 5, it is understood that a larger amount of the ultraviolet absorber was dissolved in ethanol in Comparative Example 5. It is presumed that in the light absorbing film containing an ultraviolet absorber, the ultraviolet absorber is contained together with a metal component such as copper, and thus some interaction such as complexation occurs, making it difficult for the ultraviolet absorber to be dissolved in an organic solvent such as ethanol.

[0134] It was suggested that when a light-absorbing film containing an ultraviolet absorber and a metal component such as copper is immersed in ethanol for 24 hours, the amount of ultraviolet absorber dissolved in the ethanol is adjusted to 10% to 40% by mass, or more quantitatively, 10% to 20%, of the ultraviolet absorber contained in the light-absorbing film.

[0135] [Table 1]

[0136] [Table 2]

[0137] [Table 3]

[0138] [Table 4]

[0139] [Table 5] [Explanation of symbols]

[0140] 1a, 1b Optical filters 10 Light absorbing film 20 Transparent dielectric substrate

Claims

1. 1. A light absorbing composition comprising a resin and a light absorbing compound dispersed in the resin, In the transmission spectrum of the light-absorbing film formed by the light-absorbing composition at an incident angle of 0 degrees, the transmittance at a wavelength of 400 nm is defined as T 400 and the transmittance at a wavelength of 550 nm is T 550 and the transmittance at a wavelength of 800 nm is T 800 Then, 8≦T 550 / T 400 and 28≦T 550 / T 800 Fulfilling Light absorbing composition.

2. 2. The light-absorbing composition according to claim 1, wherein the light-absorbing film satisfies the following (i) to (x) in a transmission spectrum at an incident angle of 0 degrees: (i) Maximum transmittance T at wavelengths of 300 nm to 380 nm M 300-380 is less than 1%. (ii) Transmittance T at a wavelength of 400 nm 400 is less than 20%. (iii) λ is a UV cutoff wavelength at which the transmittance is 50% in the wavelength range of 400 nm to 490 nm. UV CF When expressed as [nm], 405 nm≦λ UV CF ≦480 nm. (iv) Average transmittance T at wavelengths of 480 nm to 580 nm A 480-580 is more than 78%. (v) λ is the IR cutoff wavelength at which the transmittance is 50% in the wavelength range of 590 nm to 700 nm. IR CF When expressed as [nm], 600 nm≦λ IR CF ≦700 nm. (vi) Average transmittance T at wavelengths of 700 nm to 750 nm A 700-750 is less than 10%. (vii) Maximum transmittance T at wavelengths of 800 nm to 950 nm M 800-950 is less than 3%. (viii) Maximum transmittance T at wavelengths of 700 nm to 1000 nm M 700-1000 is less than 10%. (ix) Maximum transmittance T at wavelengths of 700 nm to 1100 nm M 700-1100 is less than 15%. (x) Maximum transmittance T at wavelengths of 700 nm to 1200 nm M 700-1200 is less than 20%.

3. 2. The light-absorbing composition according to claim 1, wherein the light-absorbing film satisfies the following (α), (β), and (γ) in a transmission spectrum at an incident angle of 0 degrees. (α) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 300 nm to 450 nm RUV 1% [nm] is 90 nm or more. (β) The wavelength at which the transmittance is 50% in the wavelength range of 590 nm to 700 nm is the IR cutoff wavelength λ IR CF The wavelength at which the transmittance is 50% in the wavelength range of 400 nm to 490 nm is the UV cutoff wavelength λ UV CF When expressed in [nm], IR cutoff wavelength λ IR CF [nm] and UV cutoff wavelength λ UV CF The difference from [nm] is 180 nm or more. (γ) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 700 nm to 1200 nm RIR 1% [nm] is 200 nm or more.

4. 4. The light-absorbing composition according to claim 1, wherein the light-absorbing film has a thickness of 10 μm to 600 μm.

5. An optical filter including a light absorbing film including a resin and a light absorbing compound, In the transmission spectrum of the light absorbing film at an incident angle of 0 degrees, the transmittance at a wavelength of 400 nm is T 400 and the transmittance at a wavelength of 550 nm is T 550 and the transmittance at a wavelength of 800 nm is T 800 Then, 8≦T 550 / T 400 and 28≦T 550 / T 800 Fulfilling Optical filters.

6. 6. The optical filter according to claim 5, wherein the optical filter satisfies the following (I) to (X) in a transmission spectrum at an incident angle of 0 degrees. (I) Maximum transmittance T at wavelengths of 300 nm to 380 nm M 300-380 is less than 1%. (II) Transmittance T at a wavelength of 400 nm 400 is less than 20%. (III) λ is a UV cutoff wavelength at which the transmittance is 50% in the wavelength range of 400 nm to 490 nm. UV CF When expressed as [nm], 405 nm≦λ UV CF ≦480 nm. (IV) Average transmittance T at wavelengths of 480 nm to 580 nm A 480-580 is more than 78%. (V) λ is the IR cutoff wavelength at which the transmittance is 50% in the wavelength range of 590 nm to 700 nm. IR CF When expressed as [nm], 600 nm≦λ IR CF ≦700 nm. (VI) Average transmittance T at wavelengths of 700 nm to 750 nm A 700-750 is less than 10%. (VII) Maximum transmittance T at wavelengths of 800 nm to 950 nm M 800-950 is less than 3%. (VIII) Maximum transmittance T at wavelengths of 700 nm to 1000 nm M 700-1000 is less than 10%. (IX) Maximum transmittance T at wavelengths of 700 nm to 1100 nm M 700-1100 is less than 15%. (X) Maximum transmittance T at wavelengths of 700 nm to 1200 nm M 700-1200 is less than 20%.

7. 6. The optical filter according to claim 5, wherein the following (α), (β), and (γ) are satisfied in a transmission spectrum of the optical filter at an incident angle of 0 degrees. (α) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 300 nm to 450 nm RUV 1% [nm] is 90 nm or more. (β) The wavelength at which the transmittance is 50% in the wavelength range of 590 nm to 700 nm is the IR cutoff wavelength λ IR CF The wavelength at which the transmittance is 50% in the wavelength range of 400 nm to 490 nm is the UV cutoff wavelength λ UV CF When expressed in [nm], IR cutoff wavelength λ IR CF [nm] and UV cutoff wavelength λ UV CF The difference from [nm] is 180 nm or more. (γ) The difference λ between the maximum wavelength showing 1% transmittance and the minimum wavelength showing 1% transmittance in the wavelength range of 700 nm to 1200 nm RIR 1% [nm] is 200 nm or more.

8. 8. The optical filter according to claim 5, wherein the light absorbing film has a thickness of 10 μm to 600 μm.

Citation Information

Patent Citations

  • Ink composition

    JP1987032161A

  • Optical filter

    JP2019028420A

  • Infrared cutoff filter, imaging device, and method for manufacturing infrared cutoff filter

    WO2017006571A1

  • Optical filter and imaging device

    WO2017094858A1

  • Light-absorbing composition, and optical filter

    WO2018088561A1